Captain Pugwash in the Secret of San Fiasco - Ryan, John (Penguin Books Ltd, 1996)
Captain Pugwash and the crew of the Black Pig are in pursuit of Spanish treasure - but why has this brought them to the rocky coast of Scotland? Legend has it that the San Fiasco, a ship of the Spanish Armada and laden with gold, vanished without trace one stormy night in Bogle Bay many years before ...
Keywords: Juvenile literature-Fiction